2020
DOI: 10.1109/tkde.2019.2896985
|View full text |Cite
|
Sign up to set email alerts
|

Semi-Supervised Deep Learning Approach for Transportation Mode Identification Using GPS Trajectory Data

Abstract: Identifying users' transportation modes (e.g., bike, bus, train, and car) is a key step towards many transportation related problems including (but not limited to) transport planning, transit demand analysis, auto ownership, and transportation emissions analysis. Traditionally, the information for analyzing travelers' behavior for choosing transport mode(s) was obtained through travel surveys. High cost, low-response rate, time-consuming manual data collection, and misreporting are the main demerits of the sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(51 citation statements)
references
References 27 publications
(45 reference statements)
0
51
0
Order By: Relevance
“…In short, semisupervised algorithms add unlabelled samples to the training data and the classifier is retrained on the new augmented training dataset. In one of the few studies in using semisupervised deep learning approaches for mode detection, Dabiri et al (2019) proposed a semi-supervised Convolutional Autoencoder architecture to predict transportation mode using GPS data. They achieved an accuracy of 76.8% with four convolutional layer, showing a decrease in accuracy in a higher number of layers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In short, semisupervised algorithms add unlabelled samples to the training data and the classifier is retrained on the new augmented training dataset. In one of the few studies in using semisupervised deep learning approaches for mode detection, Dabiri et al (2019) proposed a semi-supervised Convolutional Autoencoder architecture to predict transportation mode using GPS data. They achieved an accuracy of 76.8% with four convolutional layer, showing a decrease in accuracy in a higher number of layers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Lu et al [21] identified the tourists of common diligence and a model that considered their travel preferences was established to learn and predict their next trip. In addition, some scholars also analyze the big data in the field of transportation to release the travel behavior of passengers [22]- [24]. Although the existing literature considers the travel characteristics of passengers, previous research rarely studies the relationship between the travel characteristics of passengers and the strategy of urban rail transit fare.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Silva et al [17] (2014) demonstrated that people's travel patterns are predominantly spatial-temporal and predictable. Dabiri et al [18] (2014) proposed a deep semi-supervised convolution auto encoder (SECA) architecture for travel pattern recognition, which not only automatically extracts relevant features from GPS segments but also utilizes unlabeled data. Tao et al [19] (2014) used smart card data and flow-comap to check the spatial-temporal dynamics of bus passenger travel behavior; their research results can provide information for local public transport policies.…”
Section: Travel Pattern Miningmentioning
confidence: 99%
“…Lu et al [23] (2019) proposed a graph-based iterative propagation learning algorithm to identify visitors from public commuters and then designed a tourism preference analysis model to learn and predict their next trip. The literature [3,[17][18][19][20][21][22][23] primarily analyzed the passenger's travel mode from a spatial and temporal perspective.…”
Section: Travel Pattern Miningmentioning
confidence: 99%